TYPICAL FEATURES OF A ROMAN IMPERIAL DENARIUS HOARD FROM THE CHERNYAKHIV CULTURE TERRITORY – THE CASE OF THE SKYPCHE HOARD FROM UKRAINE - Kyrylo Myzgin; Arkadiusz Dymowski; Oleksiy Chemuranov (Journal of Ancient History and Archaeology)
The hoard found in 2018 at Skypche in the western region of Ukraine included seventy Roman denarii of the 1st and 2nd century AD (Trajan to Commodus) and a presumably silver ring. The hoard is typical for the territory of Ukraine occupied in the later phases of the Roman period and the Migration period by the people of the Chernyakhiv culture identified with a federation of Gothic and non-Gothic peoples under the Gothic leadership. Among the coins in the hoard was one barbarian imitation of a Roman denarius and seven denarii weighing of less than 2 g identified initially as of official issue. Some of the lightweight denarii could be copies of Roman denarii. It is not unlikely that these copies were manufactured within the Barbaricum.